Coated quantum dot, quantum dot adhesive, preparation method thereof and LED light source
By using clad quantum dots in LED light sources, using alloy core-shell structures and copolymers, silica and antioxidants to form clad layers, the luminescence problem caused by quantum dot oxidation is solved and the luminescence of LED light sources is improved Efficiency, color gamut and stability.
Patent Information
- Application Number
- CN202411236871.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-04
- Publication Date
- 2024-12-20
AI Technical Summary
Quantum dots in existing LED light sources are prone to oxidation, resulting in poor luminescence life, luminescence effect and color gamut, and low color gamut and color purity.
The coated quantum dots are adopted to form a cladding layer through the coordinated interaction between the red and green quantum dots of the alloy core-shell structure and copolymers, silica and antioxidants to improve the antioxidant and light resistance of the quantum dots. Enhance luminescence efficiency and color gamut.
It significantly improves the luminous efficiency, color gamut and stability of LED light sources, extends service life, and improves color purity and chemical stability.
Smart Images

Figure CN119161875A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of LEDs, and in particular relates to a coated quantum dot, a quantum dot glue, a preparation method thereof and an LED light source. Background Art
[0002] LED (Light Emitting Diode) light sources have the advantages of small size, long life, and high efficiency, and have been widely used as backlight sources in display devices.
[0003] LED light sources usually use yellow phosphors synthesized from red phosphors and green phosphors as fluorescent materials. Under the excitation of blue light chips, the light emitted by the yellow phosphors can be mixed with the blue light to form white light. In order to ensure that the phosphors can obtain sufficient excitation energy, the power and light output of the blue light chips configured in LED light sources are required to be high, and the absorption intensity of the phosphors at the corresponding wavelengths is also low, which results in relatively low color gamut and color purity of traditional LED light sources.
[0004] The existing technology uses quantum dots as fluorescent materials for LED light sources in the hope that LED light sources have a wider color gamut, higher color purity and luminous efficiency. However, in the application process of LED light sources, quantum dots will quickly oxidize when exposed to air for a long time or under the action of blue light, which seriously inhibits their thermal stability and photoluminescence / electroluminescence efficiency, resulting in poor luminous life, luminous effect and color gamut of LED light sources.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] The present application provides a coated quantum dot, a quantum dot glue, a preparation method thereof and an LED light source, aiming to solve or improve at least one of the above-mentioned defects.
[0007] The first aspect of the present application provides a coated quantum dot, the raw materials of the coated quantum dot include a quantum dot composition and a copolymer mixture; the components of the quantum dot composition include red light quantum dots and green light quantum dots with an alloy core-shell structure; the components of the copolymer mixture include a copolymer, silica and an antioxidant; wherein the copolymer is used to form a coating layer on the surface of the red light quantum dots and the green light quantum dots under the synergistic action of silica and the antioxidant.
[0008] The coated quantum dots provided in the present application mainly use a quantum dot composition and a copolymer mixture as raw material components, wherein the quantum dot composition is mainly composed of red light quantum dots and green light quantum dots of an alloy core-shell structure. These quantum dots have a high degree of environmental adaptability due to their unique alloy core-shell design and present a narrow luminescence peak, which significantly improves the quantum yield of the quantum dots, so that the LED light source has a higher NTSC color gamut and color purity. Moreover, the alloy core-shell structure can effectively suppress the surface defects of the red light quantum dots and the green light quantum dots, and the equal-bandgap material of the shell layer can protect the core, so that the red light quantum dots and the green light quantum dots have higher antioxidant and light resistance, so as to improve the luminous efficiency, color gamut and chemical stability of the LED light source during the packaging process;
[0009] Among the copolymer mixture components, the copolymer, as a key component, can closely cooperate with silica and antioxidants in the process of transforming from a glass state to a highly elastic state, and together form a uniform coating layer on the surface of red light quantum dots and green light quantum dots. The coating layer formed by the synergistic compatibility of each component can effectively regulate the surface ligands and charges of the shell structure of red light quantum dots and green light quantum dots, and play a buffering and isolating role to reduce the contact opportunities between internal quantum dots and external substances, thereby inhibiting the rearrangement of atoms on the surface of quantum dots and the formation of intermediate energy level defect states; moreover, in the LED light source made of coating layer quantum dots with UV glue, the coating layer can inhibit the color gamut reduction of the LED light source caused by the photooxidation of red light quantum dots and green light quantum dots under strong blue light excitation. The coated quantum dots have higher antioxidant stability and are not easy to aggregate in UV glue. At the same time, the coating layer can provide a more similar refractive environment for the internal red light quantum dots and green light quantum dots and the external UV glue, further reducing the optical loss in the light conduction process, so that the luminous efficiency of the LED light source is significantly improved.
[0010] Therefore, the present application designs coated quantum dots so that the structural component effects of the coating layer comprehensively suppress the attenuation of quantum dots under blue light excitation. The synergistic effect of the components of the coated quantum dots enables the LED light source to achieve significant improvements in luminous efficiency, color gamut, stability and service life during application.
[0011] In some embodiments, the encapsulated quantum dots satisfy at least one of the following conditions:
[0012] A. The mass ratio of the quantum dot composition to the copolymer mixture is 1:(1.25-5);
[0013] B. The red light quantum dots and the green light quantum dots are at least one of group II-VI quantum dots and group I-II-VI quantum dots;
[0014] C. The luminescence peak range of red quantum dots is 620nm-680nm;
[0015] D. The green quantum dot emission peak range is 510nm-550nm;
[0016] E. The mass ratio of red light quantum dots to green light quantum dots is 1:(3-8);
[0017] F. The glass transition temperature of the copolymer is 100-130°C;
[0018] G. The ratio of the total mass of the red light quantum dots and the green light quantum dots to the total mass of the copolymer is 1:(0.25-2);
[0019] H. Silica is nano-sized silica;
[0020] I. The mass ratio of copolymer to silicon dioxide is 1:(0.025-0.3);
[0021] J. The mass ratio of copolymer to antioxidant is 1:(0.025-0.2).
[0022] In some embodiments, the encapsulated quantum dots satisfy at least one of the following conditions:
[0023] K, II-VI group quantum dots including at least one of CdSe, CdS, ZnSe, ZnS, CdZnS, CdZnSe, ZnSeS, CdSeS or CdZnSeS;
[0024] L. Group I-II-VI quantum dots include at least one of CuSe, CuS, CuZnSe, CuZnS or CuCdZnSSe;
[0025] M, a copolymer comprising at least one of poly(methyl methacrylate-co-ethyl acrylate), polystyrene maleic anhydride copolymer, isopropylene maleic anhydride copolymer, poly(methyl methacrylate-co-methacrylic acid), polyisobutyl methacrylate, polybutyl methacrylate, or poly(ethyl methacrylate);
[0026] N. The antioxidant includes at least one of antioxidants 168, 264, 702, 1010, 1024 or 1076.
[0027] In some embodiments, the components of the quantum dot composition also include organic solvent A; the components of the copolymer mixture also include organic solvent B; optionally, the mass ratio of the total mass of the red light quantum dots and the green light quantum dots to the organic solvent A is 1:(1.25-5); optionally, the mass ratio of the copolymer to the organic solvent B is 1:(15-25); optionally, the organic solvent A or the organic solvent B includes at least one of toluene, xylene, n-hexane, and chloroform.
[0028] The second aspect of the present application provides a method for preparing the above-mentioned coated quantum dots, comprising:
[0029] The quantum dot composition preparation process comprises: mixing red light quantum dots and green light quantum dots in a predetermined ratio and dispersing the mixed mixture in an organic solvent A to obtain a quantum dot composition;
[0030] Preparation process of copolymer mixture: after the copolymer and organic solvent A are mixed and reacted, silicon dioxide and antioxidant are added to react to obtain a copolymer mixture;
[0031] The encapsulated quantum dot synthesis process is as follows: the quantum dot composition is mixed with the copolymer mixture for reaction, and the encapsulated quantum dots are obtained after post-treatment.
[0032] In some embodiments, the copolymer mixture preparation process specifically includes: mixing the copolymer and the organic solvent B in a predetermined ratio and reacting them at a first preset temperature for 1 to 2 hours, then adding silicon dioxide and an antioxidant and continuing the reaction for 0.2 to 1 hour to obtain a copolymer mixture;
[0033] The encapsulated quantum dot synthesis process specifically includes: mixing the quantum dot composition and the copolymer mixture, reacting at a second preset temperature for 3 to 5 hours, and obtaining the encapsulated quantum dots after distillation and drying;
[0034] Optionally, the first preset temperature is 100-130°C; preferably 110-130°C;
[0035] Optionally, the second preset temperature is 100-110°C; preferably 100-105°C.
[0036] The third aspect of the present application provides a quantum dot glue, whose raw materials include the above-mentioned coated quantum dots, UV glue prepolymer, photoinitiator and monomer liquid; the monomer liquid can undergo cross-linking polymerization reaction with the UV glue prepolymer, and the monomer liquid includes monomer liquid A, monomer liquid B and monomer liquid C; wherein monomer liquid A is used to disperse the coated quantum dots, monomer liquid B is used to dilute the UV glue prepolymer, and monomer liquid C is used to dissolve the photoinitiator.
[0037] In some embodiments, the quantum dot glue satisfies at least one of the following conditions:
[0038] a. The UV glue prepolymer includes at least one of epoxy acrylate, polyurethane acrylate, polyether acrylate, polyester acrylate or acrylic resin;
[0039] b. The monomer liquid is selected from at least one of an acrylic acid ester monomer liquid, an acrylonitrile monomer liquid, an aromatic vinyl monomer liquid, a diene monomer liquid, a vinyl halide monomer liquid or a vinyl ether monomer liquid;
[0040] c. The photoinitiator includes at least one of photoinitiator TPO, 1173, 184, 907, 369, 1490, 1700, 1010 or benzophenone;
[0041] d. The mass ratio of the coated quantum dots to the monomer liquid A is 1:(0.5-2);
[0042] e. The mass ratio of monomer liquid B to UV adhesive prepolymer is 1:(1-5);
[0043] f. The mass ratio of monomer liquid C to photoinitiator is: 1:(0.1-0.6);
[0044] g. The mass ratio of UV glue prepolymer to photoinitiator is 1:(0.025-0.075);
[0045] h. The mass ratio of UV glue prepolymer to coated quantum dots is 1:(0.15-0.45).
[0046] The fourth aspect of the present application provides a method for preparing the quantum dot glue as described above, comprising the following steps:
[0047] Mixing and dissolving the photoinitiator with the monomer liquid C to obtain a photoinitiator dissolved in the monomer liquid C;
[0048] Mixing the coated quantum dots with the monomer liquid A to obtain the coated quantum dots dispersed in the monomer liquid A;
[0049] After the monomer liquid B is mixed with the UV glue prepolymer and subjected to a first vacuum degassing treatment, a photoinitiator dissolved in the monomer liquid C is added to perform a second vacuum degassing treatment, and then the coated quantum dots dispersed in the monomer liquid A are added to perform a third vacuum degassing treatment to obtain quantum dot glue;
[0050] Optionally, the first vacuum degassing treatment lasts for 15 to 25 minutes;
[0051] Optionally, the second vacuum degassing treatment lasts for 5 to 15 minutes;
[0052] Optionally, the third vacuum degassing treatment lasts for 15 to 25 minutes.
[0053] A fifth aspect of the present application provides an LED light source, comprising a substrate and a quantum dot glue layer formed by the quantum dot glue as described above loaded on the substrate. BRIEF DESCRIPTION OF THE DRAWINGS
[0054] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0055] Figure 1 A schematic diagram of the structure of an LED light source provided by an exemplary embodiment of the present invention;
[0056] Figure 2 This is a color gamut change diagram before and after the continuous blue light irradiation efficiency attenuation test of the quantum dot glue prepared in Example 1 of the present invention (the left side is the initial NTSC color gamut at 0h, and the right side is the NTSC color gamut after the 3000h attenuation test);
[0057] Figure 3 This is a color gamut change diagram before and after the continuous blue light irradiation efficiency attenuation test of the quantum dot glue prepared in Example 2 of the present invention (the left side is the initial NTSC color gamut at 0h, and the right side is the NTSC color gamut after the 3000h attenuation test);
[0058] Figure 4 This is a color gamut change diagram before and after the continuous blue light irradiation efficiency attenuation test of the quantum dot glue prepared in Example 3 of the present invention (the left side is the initial NTSC color gamut at 0h, and the right side is the NTSC color gamut after the 3000h attenuation test);
[0059] Figure 5 This is a color gamut change diagram before and after the continuous blue light irradiation efficiency attenuation test of the quantum dot glue prepared in Example 4 of the present invention (the left side is the initial NTSC color gamut at 0h, and the right side is the NTSC color gamut after the 3000h attenuation test);
[0060] Figure 6 This is a color gamut change diagram before and after the continuous blue light irradiation efficiency attenuation test of the quantum dot glue prepared in Example 5 of the present invention (the left side is the initial NTSC color gamut at 0h, and the right side is the NTSC color gamut after the 3000h attenuation test);
[0061] Figure 7 This is a color gamut change diagram before and after the continuous blue light irradiation efficiency attenuation test of the quantum dot glue prepared in Example 6 of the present invention (the left side is the initial NTSC color gamut at 0h, and the right side is the NTSC color gamut after the 3000h attenuation test);
[0062] Figure 8 This is a color gamut change diagram of the quantum dot glue prepared in Comparative Example 1 of the present invention before and after the continuous blue light irradiation efficiency attenuation test (the left side is the initial NTSC color gamut at 0h, and the right side is the NTSC color gamut after the 3000h attenuation test);
[0063] Fig. 9This is a color gamut change diagram of the quantum dot glue prepared in comparative example 2 of the present invention before and after the continuous blue light irradiation efficiency attenuation test (the left side is the initial NTSC color gamut at 0h, and the right side is the NTSC color gamut after the 3000h attenuation test);
[0064] Fig.10 This is a color gamut change diagram of the quantum dot glue prepared in comparative example 3 of the present invention before and after the continuous blue light irradiation efficiency attenuation test (the left side is the initial NTSC color gamut at 0h, and the right side is the NTSC color gamut after the 3000h attenuation test);
[0065] Fig.11 This is a color gamut change diagram of the quantum dot glue prepared in comparative example 4 of the present invention before and after the continuous blue light irradiation efficiency attenuation test (the left side is the initial NTSC color gamut at 0h, and the right side is the NTSC color gamut after the 3000h attenuation test);
[0066] Fig.12 This is a color gamut change diagram of the quantum dot glue prepared in comparative example 5 of the present invention before and after the continuous blue light irradiation efficiency attenuation test (the left side is the initial NTSC color gamut at 0h, and the right side is the NTSC color gamut after the 3000h attenuation test);
[0067] Fig.13 This is a color gamut change diagram of the quantum dot glue prepared in Example 1 of the present invention before and after the luminous efficiency attenuation test in a light-proof environment (the left side is the initial NTSC color gamut at 0h, and the right side is the NTSC color gamut after the 3000h attenuation test);
[0068] Fig.14 This is a color gamut change diagram of the quantum dot glue prepared in Example 2 of the present invention before and after the luminous efficiency attenuation test in a light-proof environment (the left side is the initial NTSC color gamut at 0h, and the right side is the NTSC color gamut after the 3000h attenuation test);
[0069] Fig.15 This is a color gamut change diagram of the quantum dot glue prepared in Example 3 of the present invention before and after the luminous efficiency attenuation test in a light-proof environment (the left side is the initial NTSC color gamut at 0h, and the right side is the NTSC color gamut after the 3000h attenuation test);
[0070] Fig.16 This is a color gamut change diagram of the quantum dot glue prepared in Example 4 of the present invention before and after the luminous efficiency attenuation test in a light-proof environment (the left side is the initial NTSC color gamut at 0h, and the right side is the NTSC color gamut after the 3000h attenuation test);
[0071] Fig.17 This is a color gamut change diagram of the quantum dot glue prepared in Example 5 of the present invention before and after the luminous efficiency attenuation test in a light-proof environment (the left side is the initial NTSC color gamut at 0h, and the right side is the NTSC color gamut after the 3000h attenuation test);
[0072] Fig.18This is a color gamut change diagram of the quantum dot glue prepared in Example 6 of the present invention before and after the luminous efficiency attenuation test in a light-proof environment (the left side is the initial NTSC color gamut at 0h, and the right side is the NTSC color gamut after the 3000h attenuation test);
[0073] Fig.19 This is a color gamut change diagram of the quantum dot glue prepared in comparative example 1 of the present invention before and after the luminous efficiency attenuation test in a light-proof environment (the left side is the initial NTSC color gamut at 0h, and the right side is the NTSC color gamut after the 3000h attenuation test);
[0074] Fig. 20 This is a color gamut change diagram of the quantum dot glue prepared in comparative example 2 of the present invention before and after the luminous efficiency attenuation test in a light-shielded environment (the left side is the initial NTSC color gamut at 0h, and the right side is the NTSC color gamut after the 3000h attenuation test);
[0075] Fig.21 This is a color gamut change diagram of the quantum dot glue prepared in comparative example 3 of the present invention before and after the luminous efficiency attenuation test in a light-shielded environment (the left side is the initial NTSC color gamut at 0h, and the right side is the NTSC color gamut after the 3000h attenuation test);
[0076] Fig. 22 This is a color gamut change diagram of the quantum dot glue obtained in comparative example 4 of the present invention before and after the luminous efficiency attenuation test in a light-proof environment (the left side is the initial NTSC color gamut at 0h, and the right side is the NTSC color gamut after the 3000h attenuation test);
[0077] Fig.23 This is a color gamut change diagram of the quantum dot glue obtained in comparative example 5 of the present invention before and after the luminous efficiency attenuation test in a light-shielded environment (the left side is the initial NTSC color gamut at 0h, and the right side is the NTSC color gamut after the 3000h attenuation test);
[0078] Fig.24 The spectra before and after the attenuation test of the continuous blue light irradiation efficiency of the quantum dot glue prepared in Comparative Example 1 of the present invention (the left side is the initial spectrum at 0h, and the right side is the spectrum after the attenuation test at 3000h). DETAILED DESCRIPTION
[0079] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0080] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0081] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0082] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0083] If there is no special explanation, the "include" and "comprising" mentioned in this application represent open-ended or closed-ended expressions. For example, the "include" and "comprising" may also include or contain other components not listed, or may only include or contain the listed components.
[0084] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0085] In accordance with the above, considering that the quantum dots in the prior art are easily exposed to the air for a long time or oxidized rapidly under the action of blue light during the application of LED light sources, resulting in poor luminous life, luminous effect and color gamut of the LED light source, the embodiment of the present application provides a coated quantum dot, the raw materials of the coated quantum dot include a quantum dot composition and a copolymer mixture; the components of the quantum dot composition include red light quantum dots and green light quantum dots of alloy core-shell structure; the components of the copolymer mixture include copolymers, silicon dioxide and antioxidants; wherein the copolymer is used to form a coating layer on the surface of the red light quantum dots and the green light quantum dots under the synergistic action of silicon dioxide and antioxidants. By designing the components of the coated quantum dots, the red light quantum dots and the green light quantum dots of the alloy core-shell structure are coated with a coating layer formed by copolymers, antioxidants and silicon dioxide, so that the LED light source made of quantum dot glue prepared by the coated quantum dots is significantly improved in terms of luminous efficiency, color gamut, stability and service life during the application process.
[0086] It should be noted that the alloy core-shell structure refers to a nanoscale ordered assembly structure with one or more alloy materials as the core and one or more alloy materials as the shell. This structure tightly combines alloy materials of different components through chemical bonds or other forces to form a composite material with unique properties. The red light quantum dots in the embodiment of the present application refer to alloy core-shell structure quantum dots that can emit red fluorescence. The core and shell can be composed of different semiconductor materials, such as CdSe / ZnS (i.e., CdZnSeS), etc., which can emit red light with a longer wavelength when excited; green light quantum dots refer to alloy core-shell structure quantum dots that can emit green fluorescence. Similar to red light quantum dots, the core and shell materials of green light quantum dots can also be composed of different semiconductor materials. When green light quantum dots are excited, they can emit green light with a shorter wavelength.
[0087] In the embodiment of the present application, the red light quantum dots and green light quantum dots of the alloy core-shell structure used in the quantum dot composition have a high degree of environmental adaptability and present a narrow luminescence peak, which limits and improves the quantum yield of the quantum dots. Specifically, the alloy core-shell structure increases the efficiency of radiative recombination by reducing non-radiative recombination pathways, thereby improving the luminous efficiency of the quantum dots, so that the LED light source can cover a wider NTSC color gamut and show higher color purity. After the red light quantum dots and green light quantum dots of the alloy core-shell structure are coated with a coating layer formed by a copolymer, an antioxidant and silica, they are applied to LED light sources. The NTSC color gamut of the LED light source can reach more than 110%, the color purity is high, and the quantum yield can reach more than 90%. Moreover, the unique alloy core-shell structure also exhibits excellent surface defect suppression ability. The outer shell layer has a larger band gap material, which can effectively isolate the external environment from the erosion of the quantum dot core, thereby significantly improving the antioxidant and light resistance of the quantum dots, which is conducive to improving the stability of the quantum dots under strong blue light excitation conditions, thereby improving the luminous life of the LED light source.
[0088] Moreover, during the coating process of the copolymer mixture, the groups on the chain segments of the copolymer coordinate with the metal ion ligands on the surface of the quantum dots to form a surface coordination bond, so as to stably isolate the coated quantum dots from the outside world, thereby inhibiting the rearrangement of atoms on the surface of the coated quantum dots and avoiding the formation of intermediate energy level defect states; silicon dioxide, as an inorganic particle, has excellent mechanical strength and thermal stability, and can be used to modify the surface of the copolymer in the coating layer to improve the mechanical strength and thermal stability of the coating layer while reducing the polymerization shrinkage of the copolymer, improving the wrapping integrity of the copolymer around each quantum dot, and providing a quantum dot carrier matrix to further optimize the optical properties; and the antioxidant can improve the antioxidant capacity of the coating layer, inhibit the oxidative degradation of the hydrophobic groups of the copolymer caused by light and high temperature, and at the same time improve the luminescence stability of the quantum dots, inhibit free radical reactions from destroying the quantum dot structure, extend the service life of the quantum dot glue made from the coated quantum dots, and ensure the stability of the color gamut coverage of the quantum dot glue. Through the design of coated quantum dots, the structural component effects of the coating layer comprehensively inhibit the attenuation of quantum dots under blue light excitation. The synergistic effect of the various components of the coated quantum dots enables the LED light source to achieve significant improvements in luminous efficiency, color gamut, stability and service life during application.
[0089] In some embodiments, the ratio of the total mass of the red light quantum dots and the green light quantum dots to the total mass of the copolymer is 1:(0.25-2). Within this ratio range, the groups on the chain segments in the copolymer are more likely to coordinate with the metal ion ligands on the surface of the quantum dots to form a surface coordination bond, so as to stably isolate the coated quantum dots from the outside world, thereby inhibiting the rearrangement of atoms on the surface of the coated quantum dots and avoiding the formation of intermediate energy level defect states.
[0090] In some embodiments, the mass ratio of the quantum dot composition to the copolymer mixture is 1:(1.25-5), which is conducive to the complete coating of the red light quantum dots and the green light quantum dots in the quantum dot composition by the copolymer mixture, so that the copolymer, silica and antioxidant are more evenly dispersed on the surface of the red light quantum dots and the green light quantum dots and form a stable coating layer, so as to improve the antioxidant capacity of the coated quantum dots and effectively improve their thermal stability and light / electroluminescence efficiency.
[0091] In the embodiment of the present application, the mass ratio of the quantum dot composition to the copolymer mixture can be 1:(1.25-5). For example, the mass ratio of the quantum dot composition to the copolymer mixture can be 1:1.25, 1:1.3, 1:1.35, 1:1.4, 1:1.45, 1:1.5, 1:1.6, 1:1.65, 1:1.7, 1:1.75, 1:1.8, 1:1.85, 1:1.9, 1:1.95, 1:2, 1:2.1, 1:2.15, 1:2.2, 1:2.25, 1:2.3, 1:2.35, 1:2.4, 1:2.45, 1:2.5, 1:2.6, 1:2.65, 1:2.7, 1:2.75, 1:2.8, 1:2.85, 1:2. 9, 1:2.95, 1:3, 1:3.1, 1:3.15, 1:3.2, 1:3.25, 1:3.3, 1:3.35, 1:3.4, 1:3.45, 1:3.5, 1:3.6, 1:3.65, 1:3.7, 1:3.75, 1:3.8, 1:3.85, 1:3.9, 1:3.95, 1:4, 1:4 .1, 1:4.15, 1:4.2, 1:4.25, 1:4.3, 1:4.35, 1:4.4, 1:4.45, 1:4.5, 1:4.6, 1:4.65, 1:4.7, 1:4.75, 1:4.8, 1:4.85, 1:4.9, 1:4.95, 1:5 or any mass ratio in the range of 1:(1.25-5).
[0092] In some embodiments, the red light quantum dots and the green light quantum dots are at least one of the II-VI group quantum dots and the I-II-VI group quantum dots; the II-VI group quantum dots and the I-II-VI group quantum dots can be in an alloy core-shell structure, have high environmental adaptability, and have a narrower luminescence peak, so as to improve the stability and quantum yield of the coated quantum dots, thereby enabling the LED light source to have a higher NTSC color gamut and color purity.
[0093] For example, in the embodiments of the present application, as red light quantum dots and / or green light quantum dots, the II-VI group quantum dots can be selected from at least one of CdSe, CdS, ZnSe, ZnS, CdZnS, CdZnSe, ZnSeS, CdSeS or CdZnSeS; the I-II-VI group quantum dots can be selected from at least one of CuSe, CuS, CuZnSe, CuZnS or CuCdZnSSe.
[0094] In some embodiments, the luminescence peak range of red quantum dots is 620nm-680nm; the luminescence peak range of green quantum dots is 510nm-550nm; by designing the luminescence peak range of red quantum dots to 620nm-680nm, and the luminescence peak range of green quantum dots to 510nm-550nm, it is beneficial for the copolymer mixture to be completely coated on the surface of red quantum dots and green quantum dots, and it helps to broaden the color gamut of coated quantum dots and improve color purity, so that the luminescence life, luminescence effect and color gamut of the LED light source are significantly improved.
[0095] In some embodiments, the mass ratio of red light quantum dots to green light quantum dots is 1:(3-8). Within this range, the copolymer is conducive to complete encapsulation of the red light quantum dots and the green light quantum dots, and is conducive to improving the color gamut of the encapsulated quantum dots and improving the color purity, thereby significantly improving the luminous life, luminous effect and color gamut of the LED light source.
[0096] In some embodiments, the glass transition temperature of the copolymer is 100-130° C.; within this temperature range, the copolymer can transform from a glassy state to a highly elastic state, and closely cooperate with silica and antioxidants to be coated on the surface of the red light quantum dots and the green light quantum dots.
[0097] In some embodiments, the silica is nanoscale silica; the particle size of nanoscale silica is in the range of 1 to 100 nm, and has a large specific surface area and surface energy, which is beneficial for providing more quantum dot carrier matrices, providing higher mechanical strength and thermal stability for the coated quantum dots, and also conducive to promoting surface modification of the copolymer, reducing the polymerization shrinkage of the copolymer, improving the wrapping integrity of the copolymer around each quantum dot, and further optimizing the optical properties of the coated quantum dots.
[0098] In some embodiments, the mass ratio of the copolymer to silica is 1:(0.025-0.3); within this range, it is beneficial to improve the surface modification of the copolymer by silica after it is transformed into a highly elastic state, and further improve the encapsulation integrity of the copolymer for red light quantum dots and green light quantum dots.
[0099] In some embodiments, the mass ratio of the copolymer to the antioxidant is 1:(0.025-0.2); within this range, it is beneficial to improve the antioxidant capacity of the coating layer, inhibit the oxidative degradation of the hydrophobic groups in the copolymer caused by light and high temperature, and at the same time improve the luminescence stability of the coated quantum dots, prevent free radical reactions from destroying the structure of the coated quantum dots, extend the service life of the quantum dot glue made from the coated quantum dots, and ensure the stability of the color gamut coverage of the quantum dot glue.
[0100] In some embodiments, the copolymer includes at least one of poly(methyl methacrylate-co-ethyl acrylate), polystyrene maleic anhydride copolymer, isopropylene maleic anhydride copolymer, poly(methyl methacrylate-co-methacrylic acid), polyisobutyl methacrylate, polybutyl methacrylate or poly(ethyl methacrylate); as copolymers, the above substances can closely cooperate with silica and antioxidants during the transition from glass state to highly elastic state, and are uniformly coated on the surface of red light quantum dots and green light quantum dots, and as copolymers, the above substances can coordinate with metal ion ligands on the surface of the coated quantum dots to form surface coordination bonding, so as to facilitate the structural stability of the coated quantum dots.
[0101] In some embodiments, the antioxidant includes at least one of antioxidants 168, 264, 702, 1010, 1024 or 1076. It should be understood that the antioxidants in the embodiments of the present application are selected from the above substances, which can improve the antioxidant capacity of the coating layer, thereby extending the service life of the quantum dot glue made of the coated quantum dots and ensuring the stability of the color gamut coverage of the quantum dot glue. The antioxidant in the embodiments of the present application can be a single antioxidant 168, 264, 702, 1010, 1024 or 1076, or a compound antioxidant obtained by mixing multiple antioxidants above.
[0102] It should be noted that antioxidants 168, 264, 702, 1010, 1024 or 1076 can be obtained from the market. For example, antioxidant 168 can be purchased from Tianjin Lisheng Chemical, and antioxidant 264 can be purchased from Nanjing Datang Chemical.
[0103] In some embodiments, the components of the quantum dot composition also include organic solvent A; by introducing organic solvent A into the quantum dot composition, the red light quantum dots and the green light quantum dots can be dispersed in the organic solvent A to form a uniformly dispersed dispersion, so as to facilitate the formation of a more uniform and complete coating layer on the surface of the red light quantum dots and the green light quantum dots after mixing with the copolymer mixture.
[0104] In some embodiments, the mass ratio of the total mass of the red light quantum dots and the green light quantum dots to the organic solvent A is 1:(1.25-5); within this mass range, the red light quantum dots and the green light quantum dots can be evenly dispersed in the organic solvent A, so as to facilitate the formation of coated quantum dots with a more complete coating layer.
[0105] In some embodiments, the components of the copolymer mixture also include an organic solvent B; the organic solvent B is used to dissolve the copolymer, so that the copolymer can be completely transformed from a glassy state to a highly elastic state during the preparation process, and stably and uniformly coated on the surface of the red light quantum dots and the green light quantum dots along with silica and antioxidants.
[0106] In some embodiments, the mass ratio of the copolymer to the organic solvent B is 1:(15-25); within this mass ratio range, the copolymer is fully dissolved and provides a reaction environment for the close coordination of the copolymer, silica and antioxidant, making the formed coating more stable.
[0107] In some embodiments, organic solvent A or organic solvent B includes at least one of toluene, xylene, n-hexane, and chloroform. All of the above substances can be used as organic solvent A or organic solvent B, and can achieve dispersion of red light quantum dots and green light quantum dots during the preparation process, as well as dissolution of copolymers.
[0108] Another embodiment of the present application provides a method for preparing the above-mentioned coated quantum dots, comprising:
[0109] The quantum dot composition preparation process comprises: mixing red light quantum dots and green light quantum dots in a predetermined ratio and dispersing the mixed mixture in an organic solvent A to obtain a quantum dot composition;
[0110] Preparation process of copolymer mixture: after the copolymer and organic solvent A are mixed and reacted, silicon dioxide and antioxidant are added to react to obtain a copolymer mixture;
[0111] The encapsulated quantum dot synthesis process is as follows: the quantum dot composition is mixed with the copolymer mixture for reaction, and the encapsulated quantum dots are obtained after post-treatment.
[0112] It can be understood that in the embodiment of the present application, red light quantum dots and green light quantum dots are mixed in a predetermined ratio and then dispersed in organic solvent A, and the obtained quantum dot composition is a dispersion containing red light quantum dots and green light quantum dots, which is conducive to the subsequent copolymer mixture. The components fully cover the red light quantum dots and green light quantum dots; in the process of preparing the copolymer mixture, the copolymer can be first dissolved in organic solvent B and then mixed with silica and an antioxidant, so that the silica and the antioxidant can be more evenly dispersed in the reaction system, so that the silica and the antioxidant can fully exert their respective properties; by mixing the quantum dot composition with the copolymer mixture and reacting it, and after post-treatment, the obtained coated quantum dots have a complete coating layer structure, which is conducive to suppressing the attenuation of quantum dots under blue light excitation, so that the LED light source can be significantly improved in terms of luminous efficiency, color gamut, stability and service life during application.
[0113] In some embodiments, the copolymer mixture preparation process specifically includes: mixing the copolymer and the organic solvent B in a predetermined ratio, stirring and reacting at a first preset temperature for 1 to 2 hours, and then adding silicon dioxide and an antioxidant to continue stirring and reacting for 0.2 to 1 hour to obtain a copolymer mixture. By mixing the copolymer and the organic solvent B in a predetermined ratio and reacting at a first preset temperature for 1 to 2 hours, the copolymer can be gradually transformed from a glassy state to a highly elastic state. After reacting at the first preset temperature for 1 to 2 hours, silicon dioxide and an antioxidant are added and continued to react for 0.2 to 1 hour, so that silicon dioxide and an antioxidant are uniformly dispersed in the reaction system, giving full play to the surface modification effect of silicon dioxide on the highly elastic copolymer and the effect of the antioxidant on inhibiting the surface oxidation rate of the copolymer.
[0114] In some embodiments, the encapsulated quantum dot synthesis process specifically includes: mixing the quantum dot composition with the copolymer mixture and reacting at a second preset temperature for 3 to 5 hours, and obtaining the encapsulated quantum dots after distillation and drying. In the encapsulated quantum dot synthesis process, the copolymer mixture is maintained at the second preset temperature, and the quantum dot composition is further injected into the copolymer mixture to react for 3 to 5 hours, so that the copolymer, silica and antioxidant are fully loaded on the surface of the red light quantum dots and the green light quantum dots to form a uniform and complete coating layer. After post-treatment such as distillation and drying, the organic solvent A and the organic solvent B are fully removed, so that the coating layer of the encapsulated quantum dots has a higher stability.
[0115] In some embodiments, the distillation step in the synthesis process of coated quantum dots adopts rotary evaporation, the distillation temperature is controlled at 70-90° C., and the distillation time is controlled at 25-35 min to facilitate the full removal of organic solvent A and organic solvent B.
[0116] In some embodiments, the first preset temperature is 100-130°C, preferably 110-130°C; the first preset temperature is within the glass transition temperature range of the copolymer, which is conducive to promoting the copolymer to completely transform from a glassy state to a highly elastic state, and is conducive to accelerating the surface modification of the highly elastic copolymer by silica and the inhibition of the surface oxidation rate of the copolymer by antioxidants. The second preset temperature is 100-110°C; preferably 100-105°C. The second preset temperature is close to the end point temperature of the copolymer transforming to a highly elastic state, which is conducive to promoting the surface modification of the highly elastic copolymer by silica and the inhibition of the surface oxidation rate of the copolymer by antioxidants, and at the same time, it is conducive to the coordination of the groups on the chain segments of the copolymer with the metal ion ligands on the surface of the quantum dots to form a surface coordination bond, and the copolymer mixture can form a complete coating layer on the surface of the red light quantum dots and the green light quantum dots.
[0117] In order to fully utilize the performance of coated quantum dots in LED light sources, another embodiment of the present application provides a quantum dot glue, whose raw materials include the above-mentioned coated quantum dots, UV glue prepolymer, photoinitiator and monomer liquid; the monomer liquid can undergo cross-linking polymerization reaction with the UV glue prepolymer, and the monomer liquid includes monomer liquid A, monomer liquid B and monomer liquid C; wherein monomer liquid A is used to disperse the coated quantum dots, monomer liquid B is used to dilute the UV glue prepolymer, and monomer liquid C is used to dissolve the photoinitiator.
[0118] In the embodiment of the present application, the raw materials of the quantum dot glue are mainly composed of coated quantum dots, UV glue prepolymers, photoinitiators and monomer liquids; wherein, the UV glue prepolymers are mainly used to form oxygen and water barrier protection for the coated quantum dots, inhibit surface defects and color gamut reduction caused by the curing of the coated quantum dots, and reduce radiation-free recombination; the photoinitiator can activate free radicals and cations under the action of light, initiate a polymerization reaction between the functional groups of the monomer liquid and the UV glue prepolymer, form a cross-linked network structure, and allow the quantum dot glue to form a solidified structure; the monomer liquid includes monomer liquid A, monomer liquid B and monomer liquid C. The monomer liquid serves as a medium for the cross-linking reaction of the UV glue prepolymer, and can undergo a cross-linking polymerization reaction with the UV glue prepolymer to regulate the viscosity of the UV glue prepolymer, so that the viscosity of the final quantum dot glue is in the range of 200-2000cps. During the preparation process, the coated quantum dots are dispersed in the monomer liquid A, the UV glue prepolymer is diluted in the monomer liquid B, and the photoinitiator is dissolved in the monomer liquid C, which is conducive to the full mixing and dispersion of each component.
[0119] It should be understood that, based on the special design of the coated quantum dots, the coating layer in the coated quantum dots can regulate the surface ligands and charges of the internal quantum dot shell structure, play a role in buffering and isolating the UV glue prepolymer and the monomer liquid, reduce the chance of direct contact between the internal quantum dots and the UV glue prepolymer and the monomer liquid, thereby inhibiting the surface rearrangement of the quantum dots and avoiding the formation of intermediate energy level defect states; moreover, in the application process of quantum dot glue, the coating layer of the coated quantum dots can reduce the color gamut reduction caused by the photo-oxidation of the internal quantum dots under strong blue light, improve the overall antioxidant stability of the coated quantum dots, and reduce the aggregation of the coated quantum dots in the quantum dot glue; in addition, in the quantum dot glue, the copolymer used in the coating layer of the coated quantum dots can also provide a more similar refractive index environment for the coated quantum dots and the UV glue formed by the UV glue prepolymer, reduce optical losses, and thus significantly improve the luminous efficiency of the LED light source.
[0120] In some embodiments, the UV glue prepolymer includes at least one of epoxy acrylate, polyurethane acrylate, polyether acrylate, polyester acrylate or acrylic resin; the above substances as UV glue prepolymers have a high degree of matching with the coated quantum dots and can effectively coat and protect the coated quantum dots.
[0121] In some embodiments, the monomer liquid is selected from at least one of acrylate monomer liquid, acrylonitrile monomer liquid, aromatic vinyl monomer liquid, diene monomer liquid, vinyl halide monomer liquid or vinyl ether monomer liquid; the above substances as monomer liquids can all undergo cross-linking polymerization reaction with UV glue prepolymer to facilitate the viscosity regulation of quantum dot glue.
[0122] In some embodiments, the photoinitiator includes at least one of photoinitiators TPO, 1173, 184, 907, 369, 1490, 1700, 1010 or benzophenone; the above substances as photoinitiators have a suitable absorption wavelength range, which is beneficial to ensure the rapid curing of quantum dot glue and form a good cross-linked network structure.
[0123] In some embodiments, the mass ratio of the coated quantum dots to the monomer liquid A is 1:(0.5-2); within this mass ratio range, it is beneficial to balance the dispersibility of the coated quantum dots and the viscosity of the colloid, thereby enabling the performance of the coated quantum dots to be effectively exerted.
[0124] In some embodiments, the mass ratio of monomer liquid B to UV glue prepolymer is 1:(1-5); within this mass ratio range, it is beneficial to adjust the viscosity and cross-linking density of the final colloid, so that the viscosity of the quantum dot glue is in the range of 200-2000cps.
[0125] In some embodiments, the mass ratio of the monomer liquid C to the photoinitiator is: 1:(0.1-0.6); within this mass ratio range, it is conducive to the effective dispersion of the photoinitiator in the monomer liquid and sufficient initiation efficiency.
[0126] In some embodiments, the mass ratio of UV glue prepolymer to photoinitiator is 1:(0.025-0.075); within this mass ratio range, it is beneficial to optimize the cross-linking speed and the curing depth of the quantum dot glue.
[0127] In some embodiments, the mass ratio of the UV glue prepolymer to the encapsulated quantum dots is 1:(0.15-0.45); within this mass ratio range, it is beneficial to maximize the optical performance and stability of the encapsulated quantum dots.
[0128] To prepare the above quantum dot glue, another embodiment of the present application provides a method for preparing quantum dot glue, comprising the following steps:
[0129] Mixing and dissolving the photoinitiator with the monomer liquid C to obtain a photoinitiator dissolved in the monomer liquid C;
[0130] Mixing the coated quantum dots with the monomer liquid A to obtain the coated quantum dots dispersed in the monomer liquid A;
[0131] After monomer liquid B is mixed with UV glue prepolymer and subjected to a first vacuum degassing treatment under stirring, a photoinitiator dissolved in monomer liquid C is added and subjected to a second vacuum degassing treatment under stirring, and then the coated quantum dots dispersed in monomer liquid A are added and subjected to a third vacuum degassing treatment under stirring to obtain quantum dot glue.
[0132] In the embodiment of the present application, the design of the first vacuum degassing treatment, the second vacuum degassing treatment and the third vacuum degassing treatment is conducive to completely removing the bubbles formed in the system and ensuring the transparency and optical properties of the quantum dot glue.
[0133] In some embodiments, the time of the first vacuum degassing treatment is 15 to 25 minutes; the time of the second vacuum degassing treatment is 5 to 15 minutes; the time of the third vacuum degassing treatment is 15 to 25 minutes; through the first vacuum degassing treatment, the second vacuum degassing treatment and the third vacuum degassing treatment, it can be ensured that the bubbles are fully removed to improve the transparency and optical properties of the quantum dot glue.
[0134] Another embodiment of the present application provides an LED light source, including a substrate and a quantum dot glue layer formed by the quantum dot glue as described above loaded on the substrate.
[0135] In some embodiments, the LED light source preparation process is as follows: the above quantum dot glue is applied to the blue light chip in the packaging bracket, and cured by UV lamp for 30 seconds to obtain a highly stable LED light source. In order to ensure that the light can be evenly distributed when the blue light chip fully excites the quantum dot glue, the coating area of the quantum dot glue should be greater than or equal to the area of the blue light chip, and the coating height should be higher than the height of the blue light chip.
[0136] For example, if Figure 1 As shown, the LED light source exemplarily provided in the present application includes a substrate a, a solid crystal silicone b, an excitation chip c, a quantum dot glue layer d, a gold wire e, and a bracket f; wherein the bracket f is fixedly connected to the substrate a, the bracket f forms a receiving cavity, the excitation chip c is a blue light chip, the excitation chip c is arranged in the receiving cavity and is connected to the solid crystal silicone b arranged at the bottom of the receiving cavity in a direction facing the substrate a, the quantum dot glue is coated on the surface of the blue light chip to form a quantum dot glue layer d in the receiving cavity, the gold wire e passes through the quantum dot glue layer d and is electrically connected to the excitation chip c, and provides an excitation voltage for the excitation chip c.
[0137] It should be noted that the substrate in the embodiment of the present application can be a packaging bracket for LED light source packaging, or a blue light chip for exciting quantum dots, or a base film of PET material, etc., all of which can be suitable for the attachment of quantum dot glue in the present application, and the present application does not impose any restrictions.
[0138] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0139] Example 1
[0140] Preparation of coated quantum dots:
[0141] 2 g of red quantum dots and 6 g of green quantum dots were mixed and then ultrasonically dispersed in 20 g of xylene until the dispersion was clear to obtain a quantum dot composition, wherein the red quantum dots were CdZnSe with a II-VI group alloy core-shell structure and a luminescence peak of 630 nm, and the green quantum dots were CdZnSe with a II-VI group alloy core-shell structure and a luminescence peak of 535 nm;
[0142] In a nitrogen environment, 2 g of poly(methyl methacrylate-co-ethyl acrylate) and 40 g of xylene were added to a light-proof container for reaction at a reaction time of 1.5 h and a reaction temperature of 110°C. Then, 0.2 g of nano-silica, 0.1 g of antioxidant 168 and 0.1 g of antioxidant 1010 were added and the reaction was continued for 0.5 h to obtain a copolymer mixture.
[0143] The prepared quantum dot composition is injected into the copolymer mixture through a syringe, and the temperature is maintained at 100°C after injection. After keeping warm for 4 hours, the solution is taken out to obtain a copolymer-coated quantum dot solution; the xylene in the obtained copolymer-coated quantum dot solution is distilled out through a rotary evaporator, and then the solution is placed in a vacuum drying oven and dried for 30 minutes to obtain coated quantum dots, wherein the rotary evaporation temperature is 85°C and the rotary evaporation time is 30 minutes.
[0144] Quantum dot glue preparation:
[0145] 35 g of polyurethane acrylate prepolymer was mixed with 7 g of monomer liquid 1,6-hexanediol diacrylate (HDDA) and subjected to the first vacuum degassing treatment for 20 minutes under stirring. Subsequently, 0.625 g of photoinitiator benzophenone dissolved in 2 g of monomer liquid 1,6-hexanediol diacrylate (HDDA) was added and subjected to the second vacuum degassing treatment for 10 minutes under stirring. Then, 6 g of coated quantum dots dispersed with 6 g of monomer liquid 1,6-hexanediol diacrylate (HDDA) were added and subjected to the third vacuum degassing treatment for 20 minutes under stirring to obtain quantum dot glue.
[0146] Preparation of LED light source: Apply quantum dot glue on the blue light chip in the packaging bracket and cure it with a high-pressure mercury lamp for 30 seconds to obtain LED lamp beads containing coated quantum dots, such as Figure 1 shown.
[0147] Example 2
[0148] Preparation of coated quantum dots:
[0149] 2 g of red quantum dots and 6 g of green quantum dots were mixed and then ultrasonically dispersed in 20 g of toluene until the dispersion was clear, to obtain a quantum dot composition, wherein the red quantum dots were CdZnSeS of II-VI group alloy core-shell structure with a luminescence peak of 630 nm, and the green quantum dots were CdZnSeS of II-VI group alloy core-shell structure with a luminescence peak of 530 nm;
[0150] In a nitrogen environment, 3 g of poly(methyl methacrylate-co-ethyl acrylate) and 50 g of toluene were added to a light-proof container for reaction at a reaction time of 1.5 h and a reaction temperature of 110° C. Then, 0.25 g of nano-silica and 0.25 g of antioxidant 1024 were added and the reaction was continued for 0.5 h to obtain a copolymer mixture.
[0151] The prepared quantum dot composition was injected into the copolymer mixture through a syringe, and the temperature was maintained at 110°C after injection. After keeping warm for 4 hours, the solution was taken out to obtain a copolymer-coated quantum dot solution. The toluene in the obtained copolymer-coated quantum dot solution was distilled out through a rotary evaporator, and then the solution was placed in a vacuum drying oven and dried for 30 minutes to obtain coated quantum dots, wherein the rotary evaporation temperature was 85°C and the rotary evaporation time was 30 minutes.
[0152] Quantum dot glue preparation:
[0153] 40 g of epoxy acrylate prepolymer was mixed with 6 g of monomer liquid isobornyl acrylate (IBOA) and 2 g of monomer liquid dicyclopentenyl ethoxy methacrylate (DCPEMA) and subjected to a first vacuum degassing treatment for 20 min under stirring. Subsequently, 0.5 g of photoinitiator 184 and 0.25 g of photoinitiator 1173 dissolved in 2.5 g of monomer liquid isobornyl acrylate (IBOA) were added and subjected to a second vacuum degassing treatment for 10 min under stirring. Then, 7 g of coated quantum dots dispersed with 7 g of monomer liquid isobornyl acrylate (IBOA) were added and subjected to a third vacuum degassing treatment for 20 min under stirring to obtain quantum dot glue.
[0154] Example 3
[0155] Preparation of coated quantum dots:
[0156] 2 g of red quantum dots and 6 g of green quantum dots were mixed and then ultrasonically dispersed in 20 g of xylene until the dispersion was clear to obtain a quantum dot composition, wherein the red quantum dots were CdZnSe with a II-VI group alloy core-shell structure and a luminescence peak of 630 nm, and the green quantum dots were CdZnSe with a II-VI group alloy core-shell structure and a luminescence peak of 535 nm;
[0157] In a nitrogen environment, 1.6 g of poly(methyl methacrylate-co-ethyl acrylate) and 40 g of xylene were added to a light-proof container for reaction. The reaction time was 1.5 h and the reaction temperature was 110°C. Then 0.2 g of nano-silica, 0.1 g of antioxidant 168 and 0.1 g of antioxidant 1010 were added and the reaction was continued for 0.5 h to obtain a copolymer mixture.
[0158] The prepared quantum dot composition is injected into the copolymer mixture through a syringe, and the temperature is maintained at 100°C after injection. After keeping warm for 4 hours, the solution is taken out to obtain a copolymer-coated quantum dot solution; the xylene in the obtained copolymer-coated quantum dot solution is distilled out through a rotary evaporator, and then the solution is placed in a vacuum drying oven and dried for 30 minutes to obtain coated quantum dots, wherein the rotary evaporation temperature is 85°C and the rotary evaporation time is 30 minutes.
[0159] Quantum dot glue preparation:
[0160] 35 g of polyurethane acrylate prepolymer was mixed with 7 g of monomer liquid 1,6-hexanediol diacrylate (HDDA) and subjected to the first vacuum degassing treatment for 20 minutes under stirring. Subsequently, 0.625 g of photoinitiator benzophenone dissolved in 2 g of monomer liquid 1,6-hexanediol diacrylate (HDDA) was added and subjected to the second vacuum degassing treatment for 10 minutes under stirring. Then, 6 g of coated quantum dots dispersed with 6 g of monomer liquid 1,6-hexanediol diacrylate (HDDA) were added and subjected to the third vacuum degassing treatment for 20 minutes under stirring to obtain quantum dot glue.
[0161] Example 4
[0162] Preparation of coated quantum dots:
[0163] 2 g of red quantum dots and 6 g of green quantum dots were mixed and then ultrasonically dispersed in 20 g of toluene until the dispersion was clear, to obtain a quantum dot composition, wherein the red quantum dots were CdZnSeS of II-VI group alloy core-shell structure with a luminescence peak of 630 nm, and the green quantum dots were CdZnSeS of II-VI group alloy core-shell structure with a luminescence peak of 530 nm;
[0164] In a nitrogen environment, 16 g of poly(methyl methacrylate-co-ethyl acrylate) and 138 g of toluene were added to a light-proof container for reaction at a reaction time of 1.5 h and a reaction temperature of 110° C. Then, 0.25 g of nano-silica and 0.25 g of antioxidant 1024 were added, and the reaction was continued for 0.5 h to obtain a copolymer mixture.
[0165] The prepared quantum dot composition was injected into the copolymer mixture through a syringe, and the temperature was maintained at 110°C after injection. After keeping warm for 4 hours, the solution was taken out to obtain a copolymer-coated quantum dot solution. The toluene in the obtained copolymer-coated quantum dot solution was distilled out through a rotary evaporator, and then the solution was placed in a vacuum drying oven and dried for 30 minutes to obtain coated quantum dots, wherein the rotary evaporation temperature was 85°C and the rotary evaporation time was 30 minutes.
[0166] Quantum dot glue preparation:
[0167] 40 g of epoxy acrylate prepolymer was mixed with 6 g of monomer liquid isobornyl acrylate (IBOA) and 2 g of monomer liquid dicyclopentenyl ethoxy methacrylate (DCPEMA) and subjected to a first vacuum degassing treatment for 20 min under stirring. Subsequently, 0.5 g of photoinitiator 184 and 0.25 g of photoinitiator 1173 dissolved in 2.5 g of monomer liquid isobornyl acrylate (IBOA) were added and subjected to a second vacuum degassing treatment for 10 min under stirring. Then, 7 g of coated quantum dots dispersed with 7 g of monomer liquid isobornyl acrylate (IBOA) were added and subjected to a third vacuum degassing treatment for 20 min under stirring to obtain quantum dot glue.
[0168] Example 5
[0169] Preparation of coated quantum dots:
[0170] 2 g of red quantum dots and 6 g of green quantum dots were mixed and then ultrasonically dispersed in 20 g of xylene until the dispersion was clear to obtain a quantum dot composition, wherein the red quantum dots were CdZnSe with a II-VI group alloy core-shell structure and a luminescence peak of 630 nm, and the green quantum dots were CdZnSe with a II-VI group alloy core-shell structure and a luminescence peak of 535 nm;
[0171] In a nitrogen environment, 2 g of poly(methyl methacrylate-co-ethyl acrylate) and 40 g of xylene were added to a light-proof container for reaction at a reaction time of 1.5 h and a reaction temperature of 110°C. Then, 0.8 g of nano-silica, 0.1 g of antioxidant 168 and 0.1 g of antioxidant 1010 were added and the reaction was continued for 0.5 h to obtain a copolymer mixture.
[0172] The prepared quantum dot composition is injected into the copolymer mixture through a syringe, and the temperature is maintained at 100°C after injection. After keeping warm for 4 hours, the solution is taken out to obtain a copolymer-coated quantum dot solution; the xylene in the obtained copolymer-coated quantum dot solution is distilled out through a rotary evaporator, and then the solution is placed in a vacuum drying oven and dried for 30 minutes to obtain coated quantum dots, wherein the rotary evaporation temperature is 85°C and the rotary evaporation time is 30 minutes.
[0173] Quantum dot glue preparation:
[0174] 35 g of polyurethane acrylate prepolymer was mixed with 7 g of monomer liquid 1,6-hexanediol diacrylate (HDDA) and subjected to the first vacuum degassing treatment for 20 minutes under stirring. Subsequently, 0.625 g of photoinitiator benzophenone dissolved in 2 g of monomer liquid 1,6-hexanediol diacrylate (HDDA) was added and subjected to the second vacuum degassing treatment for 10 minutes under stirring. Then, 6 g of coated quantum dots dispersed with 6 g of monomer liquid 1,6-hexanediol diacrylate (HDDA) were added and subjected to the third vacuum degassing treatment for 20 minutes under stirring to obtain quantum dot glue.
[0175] Example 6
[0176] Preparation of coated quantum dots:
[0177] 2 g of red quantum dots and 6 g of green quantum dots were mixed and then ultrasonically dispersed in 20 g of toluene until the dispersion was clear, to obtain a quantum dot composition, wherein the red quantum dots were CdZnSeS of II-VI group alloy core-shell structure with a luminescence peak of 630 nm, and the green quantum dots were CdZnSeS of II-VI group alloy core-shell structure with a luminescence peak of 530 nm;
[0178] In a nitrogen environment, 3 g of poly(methyl methacrylate-co-ethyl acrylate) and 50 g of toluene were added to a light-proof container for reaction at a reaction time of 1.5 h and a reaction temperature of 110° C. Then, 0.25 g of nano-silica and 0.7 g of antioxidant 1024 were added and the reaction was continued for 0.5 h to obtain a copolymer mixture.
[0179] The prepared quantum dot composition was injected into the copolymer mixture through a syringe, and the temperature was maintained at 110°C after injection. After keeping warm for 4 hours, the solution was taken out to obtain a copolymer-coated quantum dot solution. The toluene in the obtained copolymer-coated quantum dot solution was distilled out through a rotary evaporator, and then the solution was placed in a vacuum drying oven and dried for 30 minutes to obtain coated quantum dots, wherein the rotary evaporation temperature was 85°C and the rotary evaporation time was 30 minutes.
[0180] Quantum dot glue preparation:
[0181] 40 g of epoxy acrylate prepolymer was mixed with 6 g of monomer liquid isobornyl acrylate (IBOA) and 2 g of monomer liquid dicyclopentenyl ethoxy methacrylate (DCPEMA) and subjected to a first vacuum degassing treatment for 20 min under stirring. Subsequently, 0.5 g of photoinitiator 184 and 0.25 g of photoinitiator 1173 dissolved in 2.5 g of monomer liquid isobornyl acrylate (IBOA) were added and subjected to a second vacuum degassing treatment for 10 min under stirring. Then, 7 g of coated quantum dots dispersed with 7 g of monomer liquid isobornyl acrylate (IBOA) were added and subjected to a third vacuum degassing treatment for 20 min under stirring to obtain quantum dot glue.
[0182] Comparative Example 1
[0183] 1.5 g of red quantum dots and 4.5 g of green quantum dots were mixed and then ultrasonically dispersed in 6 g of monomer liquid 1,6-hexanediol diacrylate (HDDA) until the dispersion liquid was clear, to obtain uncoated quantum dots, wherein the red quantum dots were CdZnSe of II-VI group alloy core-shell structure with a luminescence peak of 630 nm, and the green quantum dots were CdZnSe of II-VI group core-shell structure with a luminescence peak of 535 nm;
[0184] 35 g of polyurethane acrylate prepolymer was mixed with 7 g of monomer liquid 1,6-hexanediol diacrylate (HDDA) and subjected to a first vacuum degassing treatment for 20 min under stirring. Subsequently, 0.625 g of photoinitiator benzophenone dissolved in 2 g of monomer liquid 1,6-hexanediol diacrylate (HDDA) was added and subjected to a second vacuum degassing treatment for 10 min under stirring. Uncoated quantum dots dispersed with 6 g of monomer liquid 1,6-hexanediol diacrylate (HDDA) were added and subjected to a third vacuum degassing treatment for 20 min under stirring to obtain quantum dot glue.
[0185] Comparative Example 2
[0186] 1.5 g of red quantum dots and 4.5 g of green quantum dots were mixed and then ultrasonically dispersed in 6 g of monomer liquid isobornyl acrylate (IBOA) until the dispersion liquid was clear to obtain uncoated quantum dots, wherein the red quantum dots were CdZnSeS of II-VI group alloy core-shell structure with a luminescence peak of 630 nm, and the green quantum dots were CdZnSeS of II-VI group alloy core-shell structure with a luminescence peak of 530 nm;
[0187] 40 g of epoxy acrylate prepolymer was mixed with 6 g of monomer liquid isobornyl acrylate (IBOA) and subjected to a first vacuum degassing treatment for 20 min under stirring. Subsequently, 0.5 g of photoinitiator 184 dissolved in 2 g of monomer liquid dicyclopentenyl ethoxy methacrylate (DCPEMA) was added and subjected to a second vacuum degassing treatment for 10 min under stirring. Then, 6 g of uncoated quantum dots dispersed with monomer liquid isobornyl acrylate (IBOA) were added and subjected to a third vacuum degassing treatment for 20 min under stirring to obtain quantum dot glue.
[0188] Comparative Example 3
[0189] Preparation of coated quantum dots:
[0190] 2 g of red quantum dots and 6 g of green quantum dots were mixed and then ultrasonically dispersed in 20 g of xylene until the dispersion was clear to obtain a quantum dot composition, wherein the red quantum dots were CdZnSe with a II-VI group alloy core-shell structure and a luminescence peak of 630 nm, and the green quantum dots were CdZnSe with a II-VI group alloy core-shell structure and a luminescence peak of 535 nm;
[0191] In a nitrogen environment, 2 g of poly(methyl methacrylate-co-ethyl acrylate) and 40 g of xylene were added to a light-proof container for reaction at a reaction time of 1.5 h and a reaction temperature of 110°C. Then, 0.1 g of antioxidant 168 and 0.1 g of antioxidant 1010 were added and the reaction was continued for 0.5 h to obtain a copolymer mixture.
[0192] The prepared quantum dot composition is injected into the copolymer mixture through a syringe, and the temperature is maintained at 100°C after injection. After keeping warm for 4 hours, the solution is taken out to obtain a copolymer-coated quantum dot solution; the xylene in the obtained copolymer-coated quantum dot solution is distilled out through a rotary evaporator, and then the solution is placed in a vacuum drying oven for drying to obtain coated quantum dots, wherein the rotary evaporation temperature is 85°C and the rotary evaporation time is 30 minutes.
[0193] Quantum dot glue preparation:
[0194] 35 g of polyurethane acrylate prepolymer was mixed with 7 g of monomer liquid 1,6-hexanediol diacrylate (HDDA) and subjected to the first vacuum degassing treatment for 20 minutes under stirring. Subsequently, 0.625 g of photoinitiator benzophenone dissolved in 2 g of monomer liquid 1,6-hexanediol diacrylate (HDDA) was added and subjected to the second vacuum degassing treatment for 10 minutes under stirring. Then, 6 g of coated quantum dots dispersed with 6 g of monomer liquid 1,6-hexanediol diacrylate (HDDA) were added and subjected to the third vacuum degassing treatment for 20 minutes under stirring to obtain quantum dot glue.
[0195] Comparative Example 4
[0196] Preparation of coated quantum dots:
[0197] 2 g of red quantum dots and 6 g of green quantum dots were mixed and then ultrasonically dispersed in 20 g of xylene until the dispersion was clear to obtain a quantum dot composition, wherein the red quantum dots were CdZnSe with a II-VI group alloy core-shell structure and a luminescence peak of 630 nm, and the green quantum dots were CdZnSe with a II-VI group alloy core-shell structure and a luminescence peak of 535 nm;
[0198] In a nitrogen environment, 2 g of poly(methyl methacrylate-co-ethyl acrylate) and 40 g of xylene were added to a light-proof container for reaction at a temperature of 110° C. for 1.5 h. 0.2 g of nano-silica was then added and the reaction was continued for 0.5 h to obtain a copolymer mixture.
[0199] The prepared quantum dot composition is injected into the copolymer mixture through a syringe, and the temperature is maintained at 100°C after injection. After keeping warm for 4 hours, the solution is taken out to obtain a copolymer-coated quantum dot solution; the xylene in the obtained copolymer-coated quantum dot solution is distilled out through a rotary evaporator, and then the solution is placed in a vacuum drying oven for drying to obtain coated quantum dots, wherein the rotary evaporation temperature is 85°C and the rotary evaporation time is 30 minutes.
[0200] Quantum dot glue preparation:
[0201] 35 g of polyurethane acrylate prepolymer was mixed with 7 g of monomer liquid 1,6-hexanediol diacrylate (HDDA) and subjected to the first vacuum degassing treatment for 20 minutes under stirring. Subsequently, 0.625 g of photoinitiator benzophenone dissolved in 2 g of monomer liquid 1,6-hexanediol diacrylate (HDDA) was added and subjected to the second vacuum degassing treatment for 10 minutes under stirring. Then, 6 g of coated quantum dots dispersed with 6 g of monomer liquid 1,6-hexanediol diacrylate (HDDA) were added and subjected to the third vacuum degassing treatment for 20 minutes under stirring to obtain quantum dot glue.
[0202] Comparative Example 5
[0203] 1.5 g of red light quantum dots and 4.5 g of green light quantum dots were mixed and ultrasonically dispersed in 6 g of monomer liquid 1,6-hexanediol diacrylate (HDDA) until the dispersion was clarified to obtain uncoated quantum dots, wherein the red light quantum dots were CdZnSe of II-VI group alloy core-shell structure with a luminescence peak of 630 nm, and the green light quantum dots were CdZnSe of II-VI group core-shell structure with a luminescence peak of 535 nm; then 0.2 g of nano-silicon dioxide, 0.1 g of antioxidant 168 and 0.1 g of antioxidant 1010 were added to the dispersed and clarified quantum dot composition, and ultrasonically dispersed again to achieve uniform dispersion.
[0204] 35 g of polyurethane acrylate prepolymer was mixed with 7 g of monomer liquid 1,6-hexanediol diacrylate (HDDA) and subjected to a first vacuum degassing treatment for 20 min under stirring. Subsequently, 0.625 g of photoinitiator benzophenone dissolved in 2 g of monomer liquid 1,6-hexanediol diacrylate (HDDA) was added and subjected to a second vacuum degassing treatment for 10 min under stirring. Uncoated quantum dots dispersed with 6 g of monomer liquid 1,6-hexanediol diacrylate (HDDA) were added and subjected to a third vacuum degassing treatment for 20 min under stirring to obtain quantum dot glue.
[0205] The raw material data of the above-mentioned Examples 1 to 6 and Comparative Examples 1 to 5 are shown in Table 1 and Table 2 below:
[0206] Table 1. Data statistics of coated / uncoated quantum dot raw materials
[0207]
[0208] Table 2. Statistics of quantum dot glue raw materials
[0209]
[0210]
[0211] To verify the advantages of the above embodiments, 5 g of the quantum dot glue prepared in Examples 1 to 6 and Comparative Examples 1 to 5 were taken and evenly coated on the surface of the PET base film by roller coating, with a coating thickness of 75 μm. The film was cured by a high-pressure mercury lamp for 30 seconds to obtain eleven single-layer quantum dot glue films. The initial color coordinates were ensured to be within the range of x=0.2400±0.005 and y=0.2000±0.005. The eleven films were placed in a blue light box for continuous blue light irradiation efficiency attenuation test. The test conditions were: the blue light wavelength was 450 nm and the light irradiance was 500 mW / cm 2 , temperature 85℃, air humidity 95%RH, irradiation time 3000; the test data are shown in Table 3.
[0212] During the test, eleven single-layer quantum dot adhesive films were placed under a wavelength of 450nm and an irradiance of 500mW / cm 2 The color coordinate CIE values at 0h, 500h, 1000h, 2000h and 3000h were tested with an illuminometer under a blue light backlight panel; the test data are shown in Table 4.
[0213] During the test, eleven single-layer quantum dot adhesive films were placed under a fixed light source kit to measure the color coordinate values when stimulating the three primary colors of red, green and blue. The corresponding color coordinate values were calculated using the color gamut calculation software to obtain the efficiency and NTSC color gamut of the eleven films at the attenuation test of 0h, 500h, 1000h, 2000h and 3000h. The test data are shown in Table 5. Figures 2 to 12 as well as Fig.24 shown.
[0214] Table 3. Continuous blue light irradiation efficiency attenuation test data statistics
[0215]
[0216]
[0217] Table 4. Continuous blue light irradiation efficiency attenuation test color coordinate CIE value data statistics
[0218]
[0219] Table 5. NTSC color gamut data statistics for continuous blue light irradiation efficiency attenuation test
[0220]
[0221] In order to simulate the condition of being stored at room temperature after being packaged on an LED blue light chip, another group of eleven single-layer quantum dot adhesive films were prepared according to the above-mentioned method for preparing quantum dot adhesive films. The eleven films were placed in an oven at 40°C in a light-proof environment to carry out a luminous efficiency attenuation test in a light-proof environment. The test data are shown in Table 6.
[0222] During the test, eleven single-layer quantum dot adhesive films were placed under a wavelength of 450nm and an irradiance of 500mW / cm 2 The color coordinate CIE values at 0h, 500h, 1000h, 2000h and 3000h were tested with an illuminometer under a blue light backlight panel; the test data are shown in Table 7.
[0223] During the test, eleven single-layer quantum dot adhesive films were placed under a fixed light source kit to measure the color coordinate values when stimulating the three primary colors of red, green, and blue. The corresponding color coordinate values were calculated using the color gamut calculation software to obtain the NTSC color gamut of four films at 0h, 500h, 1000h, 2000h, and 3000h of attenuation test. The test data are shown in Table 8 and Figures 13 to 23 shown.
[0224] Table 6. Statistical table of luminous efficiency attenuation test data in light-proof environment
[0225]
[0226] Table 7. Statistics of color coordinates CIE values of luminous efficiency attenuation test in light-proof environment
[0227]
[0228]
[0229] Table 8. NTSC color gamut data statistics for luminous efficiency attenuation test in a dark environment
[0230]
[0231] Combined with the above Tables 1 to 8 and the following Figures 2 to 24It can be seen that, compared with Examples 1 to 2 of the present application and Comparative Examples 1 to 5, Examples 1 to 2 all use copolymers, silica and antioxidants to co-coat red light quantum dots and green light quantum dots to prepare coated quantum dots, while the red light quantum dots and green light quantum dots in Comparative Examples 1 to 5 are not coated with copolymers, silica and antioxidants at the same time. Under continuous blue light irradiation, after 3000 attenuation tests, the efficiency attenuation ratio Δ of Examples 1 to 5 does not exceed 0.96%, the color coordinate deviation Δx does not exceed 0.0017, Δy does not exceed 0.0011, and the color gamut coverage change Δ does not exceed 0.67%. In the luminous efficiency attenuation test in a light-shielded environment, the luminous efficiency attenuation ratio Δ of Examples 1 and 2 does not exceed 0.04%. The color coordinate deviation Δx does not exceed 0.0005, Δy does not exceed 0.0003, and the color gamut coverage change Δ does not exceed 0.04%; on the other hand, in comparative examples 1 to 5, the quantum dot glue films of comparative examples 1 to 5 have an efficiency attenuation ratio Δ of more than 13.27% after 3000 attenuation tests under continuous blue light irradiation, a color coordinate deviation Δx of more than 0.0297, Δy of more than 0.0288, and a color gamut coverage change Δ of more than 10.90%. In addition, in the luminous efficiency attenuation test in a light-proof environment, the luminous efficiency attenuation ratio Δ of comparative examples 1 to 5 is more than 5.21%, the color coordinate deviation Δx of more than 0.0107, Δy of more than 0.0096, and a color gamut coverage change Δ of more than 6.20%.
[0232] It can be seen that the quantum dot glue made of coated quantum dots in Examples 1 and 2 and the quantum dot glue made of quantum dots not coated with copolymers in Comparative Examples 1 to 5 have obvious differences in attenuation rate under conventional light-proof environment and continuous blue light irradiation. This verifies that the copolymer coating in Examples 1 and 2 regulates the surface ligands and charges of the outer shell structure of the quantum dots, and can play a role in buffering and isolating the UV glue prepolymer / monomer liquid, reducing the chance of direct contact between the quantum dots and the UV glue prepolymer / monomer liquid, inhibiting the rearrangement of atoms on the surface of the quantum dots, and avoiding the formation of intermediate energy level defect states. Moreover, the coating layer containing the copolymer can reduce the color gamut reduction caused by photo-oxidation of quantum dots under strong blue light, improve its antioxidant stability, and reduce the aggregation of internal quantum dots in UV glue. At the same time, the copolymer provides a more similar refractive index environment for the internal quantum dots and the UV glue, effectively reducing optical losses.
[0233] Furthermore, compared with Example 1, the difference between Example 3 is that the ratio of the total mass of red light quantum dots and green light quantum dots in the raw materials of Example 3 to the total mass of the copolymer is lower than 1:(0.25-2). After the quantum dot adhesive film of Example 3 is subjected to 3000 attenuation tests under continuous blue light irradiation, as well as in the luminous efficiency attenuation test in a light-proof environment, compared with Example 1, the efficiency, color gamut coverage and stability of the quantum dot adhesive film are greatly attenuated; this indicates that the ratio of the total mass of red light quantum dots and green light quantum dots to the total mass of the copolymer is in the range of 1:(0.25-2), which is more conducive to inhibiting the attenuation of quantum dots under blue light excitation, thereby significantly improving the stability, luminous life, luminous effect and color gamut of the LED light source.
[0234] Compared with Example 1, Example 4 is different in that the mass ratio of the quantum dot composition to the copolymer mixture in Example 4 exceeds the range of 1:(1.25-5). After the quantum dot adhesive film of Example 4 is subjected to 3000 attenuation tests under continuous blue light irradiation, as well as in the luminous efficiency attenuation test in a light-proof environment, the efficiency, color gamut coverage and stability of the quantum dot adhesive film are greatly attenuated compared with Example 1. This indicates that the mass ratio of the quantum dot composition to the copolymer mixture is within the range of 1:(1.25-5), which is more conducive to inhibiting the attenuation of quantum dots under blue light excitation, thereby significantly improving the stability, luminous life, luminous effect and color gamut of the LED light source.
[0235] Compared with Example 1, the mass ratio of the copolymer to silicon dioxide in the coated quantum dot raw material of Example 5 exceeds 1:0.025-0.3. After the quantum dot glue made of the quantum dot glue in Example 5 is subjected to a 3000 attenuation test under continuous blue light irradiation, as well as a luminous efficiency attenuation test in a light-proof environment, the efficiency, color gamut coverage and stability of the quantum dot glue film are greatly attenuated compared with Example 1; this indicates that the mass ratio of the copolymer to silicon dioxide is in the range of 1:0.025-0.3, which is more conducive to inhibiting the attenuation of quantum dots under blue light excitation, thereby significantly improving the stability, luminous life, luminous effect and color gamut of the LED light source.
[0236] Compared with Example 1, Example 6 differs in that the mass ratio of the copolymer to the antioxidant in Example 5 exceeds 1:(0.025-0.2). After the quantum dot adhesive film made of the quantum dot adhesive in Example 6 is subjected to a 3000 attenuation test under continuous blue light irradiation, as well as a luminous efficiency attenuation test in a light-proof environment, the efficiency, color gamut coverage and stability of the quantum dot adhesive film are greatly attenuated compared to Example 1; this indicates that the mass ratio of the copolymer to the antioxidant is within the range of 1:(0.025-0.2), which is more conducive to inhibiting the attenuation of quantum dots under blue light excitation, thereby significantly improving the stability, luminous life, luminous effect and color gamut of the LED light source.
[0237] In summary, the embodiment of the present application uses the design of coated quantum dots so that the structural component effects of the coating layer comprehensively suppress the attenuation of quantum dots under blue light excitation, and the synergistic effect of the various components of the coated quantum dots enables the LED light source to achieve significant improvements in luminous efficiency, color gamut, stability and service life during application.
[0238] The various technical features described above can be combined arbitrarily. Although all possible combinations of these technical features are not described, any combination of these technical features should be considered to be covered by this specification as long as there is no contradiction in such combination.
[0239] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
Claims
1. A coated quantum dot, characterized in that: The raw materials of the coated quantum dots include a quantum dot composition and a copolymer mixture; The components of the quantum dot composition include red light quantum dots and green light quantum dots of alloy core-shell structure; The components of the copolymer mixture include copolymer, silicon dioxide and antioxidant; Wherein, the copolymer is used to form a coating layer on the surface of the red light quantum dots and the green light quantum dots under the synergistic effect of the silicon dioxide and the antioxidant.
2. The encapsulated quantum dot according to claim 1, characterized in that: Satisfy at least one of the following conditions A to I: A. The mass ratio of the quantum dot composition to the copolymer mixture is 1:(1.25-5); B. The red light quantum dots and the green light quantum dots are at least one of group II-VI quantum dots and group I-II-VI quantum dots; C. The luminescence peak range of the red light quantum dots is 620nm-680nm; D. The green light quantum dot emission peak range is 510nm-550nm; E. The mass ratio of the red light quantum dots to the green light quantum dots is 1:(3-8); F. The glass transition temperature of the copolymer is 100-130°C; G. The ratio of the total mass of the red light quantum dots and the green light quantum dots to the total mass of the copolymer is 1:(0.25-2); H. The silicon dioxide is nano-scale silicon dioxide; I. The mass ratio of the copolymer to the silicon dioxide is 1:(0.025-0.3); J. The mass ratio of the copolymer to the antioxidant is 1:(0.025-0.2).
3. The encapsulated quantum dot according to claim 2, characterized in that: Satisfy at least one of the following conditions J to M: K. The II-VI group quantum dots include at least one of CdSe, CdS, ZnSe, ZnS, CdZnS, CdZnSe, ZnSeS, CdSeS or CdZnSeS; L. The I-II-VI group quantum dots include at least one of CuSe, CuS, CuZnSe, CuZnS or CuCdZnSSe; M, the copolymer comprises at least one of poly(methyl methacrylate-co-ethyl acrylate), polystyrene maleic anhydride copolymer, isopropylene maleic anhydride copolymer, poly(methyl methacrylate-co-methacrylic acid), polyisobutyl methacrylate, polybutyl methacrylate or poly(ethyl methacrylate); N. The antioxidant includes at least one of antioxidants 168, 264, 702, 1010, 1024 or 1076.
4. The encapsulated quantum dot according to any one of claims 1 to 3, characterized in that: The components of the quantum dot composition also include an organic solvent A; the components of the copolymer mixture also include an organic solvent B; Optionally, the mass ratio of the total mass of the red light quantum dots and the green light quantum dots to the organic solvent A is 1:(1.25-5); Optionally, the mass ratio of the copolymer to the organic solvent B is 1:(15-25); Optionally, the organic solvent A or organic solvent B includes at least one of toluene, xylene, n-hexane and chloroform.
5. A method for preparing a coated quantum dot according to any one of claims 1 to 4, characterized in that: include: The quantum dot composition preparation process comprises: mixing red light quantum dots and green light quantum dots in a predetermined ratio and dispersing the mixed mixture in an organic solvent A to obtain a quantum dot composition; Preparation process of copolymer mixture: after the copolymer and organic solvent A are mixed and reacted, silicon dioxide and antioxidant are added to react to obtain a copolymer mixture; The encapsulated quantum dot synthesis step is: mixing the quantum dot composition with the copolymer mixture to react, and obtaining the encapsulated quantum dots after post-treatment.
6. The method for preparing coated quantum dots according to claim 5, characterized in that: The copolymer mixture preparation process specifically comprises: mixing the copolymer and the organic solvent B in a predetermined ratio and reacting them at a first preset temperature for 1 to 2 hours, then adding silicon dioxide and an antioxidant and continuing the reaction for 0.2 to 1 hour to obtain the copolymer mixture; Optionally, the encapsulated quantum dot synthesis step specifically includes: mixing the quantum dot composition and the copolymer mixture, reacting at a second preset temperature for 3 to 5 hours, and obtaining encapsulated quantum dots after distillation and drying; Optionally, the first preset temperature is 110-130°C; Optionally, the second preset temperature is 100-110°C.
7. A quantum dot glue, characterized in that: The raw materials include the encapsulated quantum dots as claimed in any one of claims 1 to 4, UV adhesive prepolymer, photoinitiator and monomer liquid; The monomer liquid can undergo a cross-linking polymerization reaction with the UV glue prepolymer, and the monomer liquid includes monomer liquid A, monomer liquid B and monomer liquid C; The monomer liquid A is used to disperse the encapsulated quantum dots, the monomer liquid B is used to dilute the UV glue prepolymer, and the monomer liquid C is used to dissolve the photoinitiator.
8. The quantum dot glue according to claim 7, characterized in that: Satisfy at least one of the following conditions a to h: a. The UV glue prepolymer includes at least one of epoxy acrylate, polyurethane acrylate, polyether acrylate, polyester acrylate or acrylic resin; b. The monomer liquid is selected from at least one of an acrylic acid ester monomer liquid, an acrylonitrile monomer liquid, an aromatic vinyl monomer liquid, a diene monomer liquid, a vinyl halide monomer liquid or a vinyl ether monomer liquid; c. The photoinitiator includes at least one of photoinitiator TPO, 1173, 184, 907, 369, 1490, 1700, 1010 or benzophenone; d. The mass ratio of the coated quantum dots to the monomer liquid A is 1:(0.5-2) e. The mass ratio of the monomer liquid B to the UV adhesive prepolymer is 1:(1-5); f. The mass ratio of the monomer liquid C to the photoinitiator is: 1:(0.1-0.6); g. The mass ratio of the UV glue prepolymer to the photoinitiator is 1:(0.025-0.075); h. The mass ratio of the UV glue prepolymer to the coated quantum dots is 1:(0.15-0.45).
9. A method for preparing a quantum dot glue as claimed in any one of claims 7 to 8, characterized in that: The following steps are involved: Mixing and dissolving the photoinitiator with the monomer liquid C to obtain a photoinitiator dissolved in the monomer liquid C; Mixing the coated quantum dots with the monomer liquid A to obtain the coated quantum dots dispersed in the monomer liquid A; After the monomer liquid B is mixed with the UV glue prepolymer and subjected to the first vacuum degassing treatment, the photoinitiator dissolved in the monomer liquid C is added for the second vacuum degassing treatment, and then the coated quantum dots dispersed in the monomer liquid A are added for the third vacuum degassing treatment to obtain quantum dot glue.
10. An LED light source, characterized in that: The invention comprises a substrate and the quantum dot glue as claimed in any one of claims 7 to 8 loaded on the substrate to form a quantum dot glue layer.
